Maine firewood study. Quarterly technical status report No. 3, March 19-June 19, 1979 - Swain, E.W. (Maine Audubon Society, Falmouth (USA), 1978)
Progress is reported on the following: the firewood demand survey, the firewood suppliers survey; firewood management assistance; and marketing mechanism analysis. (MHR)